Organized Hybrid Molecular Films from Natural Phospholipids and Synthetic Block Copolymers A Physicochemical Investigation - Balestri, Arianna (Langmuir : the ACS journal of surfaces and colloids, 2020)
In the last few years, hybrid lipid-copolymer assemblies have attracted increasing attention as possible two-dimensional (2D) membrane platforms, combining the biorelevance of the lipid building blocks with the stability and chemical tunability of copolymers. The relevance of these systems varies from fundamental studies on biological membrane-related phenomena to the construction of 2D complex devices for material science and biosensor technology. Both the fundamental understanding and the application of hybrid lipid-copolymer-supported bilayers require thorough physicochemical comprehension and structural control. Herein, we report a comprehensive physicochemical and structural characterization of hybrid monolayers at the air/water interface and of solid-supported hybrid membranes constituted by 1,2-dipalmitoyl-sn-glycero-3-phosphocholine (DPPC) and the block copolymer poly(butadiene-b-ethyleneoxide) (PBD-b-PEO). Hybrid lipid-copolymer supported bilayers (HSLBs) with variable copolymer contents were prepared through spontaneous rupture and fusion of hybrid vesicles onto a hydrophilic substrate. The properties of the thin films and the parent vesicles were probed through dynamic light scattering (DLS), differential scanning calorimetry (DSC), optical ellipsometry, quartz crystal microbalance with dissipation monitoring (QCM-D), and confocal scanning laser microscopy (CSLM). Stable, hybrid lipid/copolymer systems were obtained for a copolymer content of 10-65 mol %. In particular, DSC and CSLM show lateral phase separation in these hybrid systems. These results improve our fundamental understanding of HSLBs, which is necessary for future applications of hybrid systems as biomimetic membranes or as drug delivery systems, with additional properties with respect to phospholipid liposomes